2015
DOI: 10.1080/03003930.2015.1127225
|View full text |Cite
|
Sign up to set email alerts
|

Political Representation and Geographical Bias in Amalgamated Local Governments

Abstract: Denmark. His research interests include political recruitment, political leadership, and local elections. His work has been published in journals such as Local Government Studies,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
2
37
0
2
Order By: Relevance
“…Citizens in municipalities that would incorporate other municipalities do not oppose this reform, in contrast to citizens in municipalities whose merger would lead to 'co-dominion' or to being 'subordinate' to another municipality. This can be explained by a fear of losing power and voice (Jakobsen and Kjaer 2015), and is in line with research that highlights the importance of representative and participatory aspects in citizens' evaluation of local democracy (Denters 2014 , p. 162). Local place attachment also only appears to impact the decision in municipalities that would amalgamate or would be incorporated.…”
Section: Discussion: Explaining Voluntary Municipal Mergers As Two-stsupporting
confidence: 78%
“…Citizens in municipalities that would incorporate other municipalities do not oppose this reform, in contrast to citizens in municipalities whose merger would lead to 'co-dominion' or to being 'subordinate' to another municipality. This can be explained by a fear of losing power and voice (Jakobsen and Kjaer 2015), and is in line with research that highlights the importance of representative and participatory aspects in citizens' evaluation of local democracy (Denters 2014 , p. 162). Local place attachment also only appears to impact the decision in municipalities that would amalgamate or would be incorporated.…”
Section: Discussion: Explaining Voluntary Municipal Mergers As Two-stsupporting
confidence: 78%
“…These findings are in line with existing research on local government amalgamation -potential scale economy benefits have been found to matter for decisions in Japanese (Miyazaki 2014) and Swiss (Strebel 2018) local merger referenda. In addition, concerns for political control are associated with municipal mergers in a variety of different contexts (Marando and Whitley 1972;Hyytinen, Saarimaa, and Tukiainen 2014;Jakobsen and Kjaer 2016;Strebel 2018). This in turn suggests that the findings of this study might be generalizable to other contexts in which local referenda on municipal mergers are held, such as Finland, Japan and the US.…”
Section: Discussionmentioning
confidence: 66%
“…For small partners, however, a merger means a substantial loss of control and self-determination. They become the minority in the new municipality and risk that their interests are given less consideration, since local representatives have an incentive to base their electoral success on the majority's interests (Jakobsen and Kjaer 2016).…”
Section: Concern For Self-determinationmentioning
confidence: 99%
“…Po trzecie, wiele państw zdecydowało się na przeprowadzenie w swoich samorządach reform strukturalno-funkcjonalnych, na przykład przez wyraźne zmniejszenie liczby gmin lub też zmianę zakresu ich zadań (zob. szerzej Kjaer, Hjelmar, Olsen, 2010;Jakobsen, Kjaer, 2016). Ponadto, zapomnieć nie można o swoistym makro-trendzie, widocznym w wielu krajach znużeniu demokracją przedstawicielską, co z kolei znajduje odzwierciedlenie w spadającej frekwencji wyborczej, rozczarowaniu partiami politycznymi, jak i rosnącej popularności kandydatów niezwiązanych z politycznym mainstreamem.…”
Section: Pp 1 '17unclassified